Knowledge, Attitude and Practice of Hepatitis-B Vaccination among Clinical Medical Students at a Medical College in Nepal - Bhattarai, Subash (Europasian Journal of Medical Sciences, 2020)
Background: Hepatitis B vaccine is the single most effective and safest strategy for the prevention of the disease among health care workers (HCW), trainees and medical students. There is scanty information on knowledge, attitude and practice (KAP) regarding Hepatitis B vaccination among medical students who are likely to get exposed in the future as they start practicing. This study was undertaken to understand the knowledge, attitude and practice of hepatitis B vaccination among clinical medical students of Manipal College of Medical sciences at Pokhara, Nepal. Methods: Two hundred and four medical students were enrolled for a descriptive cross-sectional study at Manipal College of Medical sciences at Pokhara, Nepal after obtaining ethical clearance from Institutional Review Committee. Answers to pre-tested questionnaire were collected. Knowledge, attitude and practice regarding Hepatitis B vaccination were studied. Results: All participants demonstrated good knowledge and positive attitude towards Hepatitis B infection and vaccination. However majority had poor practice towards it. Only 47.1% were completely vaccinated. The most common reason for non vaccination was that many thought they will vaccinate in internship or when they start practicing. Conclusions: Despite good knowledge and positive attitude towards Hepatitis B infection and vaccination, low rates of vaccination and poor practice was observed among medical students indicating the necessity of encouragement for vaccination and proper practices among them. All medical students should be immunized against Hepatitis B during their medical school. Regular Hepatitis B vaccination, educational and awareness programs must be conducted in coordination and with active participation of the medical students.